Potato Prawn Cheese Ball sebagai Produk Potensial untuk Meningkatkan Daya Saing UMKM - Malikah Alya Azzahra; Komang Windasari; Najua Fauzani; Karyadi Hidayat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Potato Prawn Cheese Ball is a culinary innovation based on local ingredients that combines potatoes, shrimp, and cheese to produce a savory taste and crunchy texture that suits the tastes of modern consumers. This research refers to Rogers' Diffusion of Innovation Theory regarding the innovation adoption process and Porter's Theory of Competitive Advantage which emphasizes the role of product differentiation in strengthening a business's position. Using a descriptive qualitative method with an autoethnographic approach, data was obtained through the researcher's direct experience in production and marketing, and supported by literature related to MSMEs, innovation, and digital marketing. The results show that Potato Prawn Cheese Ball has advantages in the combination of unique ingredients, modern packaging, and the potential for development as a contemporary snack product or frozen food. The innovation process was carried out through recipe trials, feedback collection, and product improvements, while the marketing strategy utilized social media and offline promotions effectively to increase market reach and sales. This innovation has been proven to have a positive impact on increasing MSME competitiveness, including increasing turnover, expanding distribution, and strengthening business image. In conclusion, the integration of product innovation and marketing digitalization makes Potato Prawn Cheese Ball a potential product that can push culinary MSMEs to the next level.